HUBUNGAN KEMANDIRIAN BELAJAR TERHADAP HASIL BELAJAR MEKANIKA TEKNIK II PADA MAHASISWA PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN UNIVERSITAS NEGERI JAKARTA - Dedi Hariyanto; R Eka Murtinugraha; Tuti Iriani (LPPM Universitas Negeri Jakarta, 2012)
The aim of this research knows the relationship between self-learning and learning output of the Mechanics of Structure II subject for the students of Building Engineering Education Program Department of Civil Engineering State University of Jakarta in June 2011 which involved 50 students as the sample of this research. The result shows that students have less initiative in utilizing the facilities served in the library, self-learning at home, learning sources, practicing in the class, and having some handouts. Discussion between students is the only indicator demonstrating that the student initiative is quite good. Unfortunately, the interest of the students regarding this subject is very low. Learning output of the Mechanics of Structure II can be categorized as worst. The reasons are the students have no confidence in preparing the materials before the test and lean on other party during the test. The student’s responsibility in using the method and media for learning this subject is good even though the students just count on the lecture notes given by the lecturers during the course. But, the allocation time and readiness aspect shows that the student’s responsibility is minus because they don’t allocate much time to digest the subject and have the tendency of studying close to the deadline. Generally, the motivation and concentration of the students in learning is high. But, in allocating more time to digest the subject is lack.